Implementation of the IHR Joint External Evaluation: Taiwan's Experiences - Lo, Yi-Chun (Health Secur, 2017)
In February 2016, the World Health Organization developed the Joint External Evaluation (JEE) tool to independently assess country capacity to prevent, detect, and respond to public health threats as part of the International Health Regulations (IHR) (2005) monitoring and evaluation framework. In light of this, the Taiwan government actively engaged at least 19 government agencies or institutions and voluntarily implemented the JEE. An External Assessment Team consisting of 6 US subject matter experts conducted the external evaluation, including site visits, from June 21 to July 1, 2016. The results, published on October 18, 2016, are useful and will be translated into actions and change in the system. Based on Taiwan's experiences, early stakeholder engagement and an experts' pre-JEE pilot visit would contribute to a successful JEE process.